Implementation of Transformative Leadership and Its Implications for 21st Century Skills in Digital Learning in High School - Prihantoro, Puthut; Sumarjoko, Bambang; Fathoni, Achmad (Universitas Muhammadiyah Surakarta, 2025)
The rapid transformation of digital education encourages secondary schools to adjust learning patterns to the demands of the 21st century. However, many principals experience confusion in changing traditional leadership practices into adaptive, inspiring, and transformative leadership styles amidst the flow of digitalization. This study aims to examine in depth the experiences of principals and teachers in implementing a transformative leadership model in the context of digital education in Senior High Schools. The research approach used is qualitative with a phenomenological method, which focuses on the subjective meaning and direct experiences of informants. Data were collected through in-depth interviews, participant observations, and documentation studies, then analyzed using thematic techniques through a manual coding process and interpretation of the meaning of experience. The results of the study indicate that transformative leadership practices emerge from a collective awareness of the importance of digital vision, an internal drive to empower teachers through technology, and a commitment to building an innovative and collaborative culture. The experiences of informants show that leadership that is value- based, reflective, and open to change plays a key role in improving students' 21st century skills. This study provides in-depth insights for school leaders and policy makers to design a more meaningful leadership approach that is oriented towards educational transformation in the era of technological disruption.